Marbling Grading Framework Applied on Meat Boutique Environment - Mastelini, Saulo Martiello; da Silva, Matheus Camilo; Barbon, Ana Paula Ayub da Costa; Barbon Jr., Sylvio (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2016)
Bovine meat commercialization has an important role in the general food market scenario. The beef quality evaluation is realized through many ways, being one of the parameters the intramuscular fat amount (marbling). This evaluation is often made by a visual approach, so the process is subjective and susceptible to some errors sources. The use of Computer Vision techniques results in an automatized, non-subjective, fast and accurate method for evaluation. This paper presents the modeling and development of a Computer Vision System for Marbling evaluation, applied on a meat Boutique, localized in Londrina – PR. The proposed System uses a Computer Vision approach to control the features of the marbling analysis tool, aiming to satisfy sanitary requirements for non-contamination of the analyzed samples. Besides that, multiples samples on the scene are supported by our application. The proposed Computer Vision System has proved to be suitable for implantation in a production environment, like a meat Boutique.